Genetic Prediction of the Phosphate‐to‐Glucose Ratio Mediates the Association Between CXCL5 and Vascular Dementia - Guifeng Zhuo; Wei Chen; Yanan Hu; Jinzhi Zhang; Xiaomin Zhu; Mingyang Su; Yulan Fu; Wu Lin (Brain and Behavior)
ABSTRACT Background and Objectives A variety of observational studies suggest a possible connection between C‐X‐C Motif Chemokine Ligand 5 (CXCL5) and vascular dementia (VaD), though the exact causal relationship is still uncertain. This research aims to investigate the causal connection between CXCL5 and VaD risk through a Mendelian randomization (MR) method and to examine the phosphate‐to‐glucose ratio as a possible mediator. Methods Using summary‐level data from genome‐wide association studies (GWAS), we conducted a two‐sample MR analysis to investigate the genetic prediction of CXCL5 and VaD. Horizontal pleiotropy, heterogeneity, and sensitivity analyses were also performed on the MR findings. Additionally, a two‐step MR was utilized to quantify the proportion of the effect of CXCL5 on VaD mediated by the phosphate‐to‐glucose ratio. Results MR analysis identified that higher levels of CXCL5 (IVW: p = 0.022, OR = 1.265, 95% CI = 1.034–1.547) increase the risk of VaD. Tests for horizontal pleiotropy (p > 0.05), heterogeneity (p > 0.05), and sensitivity analyses supported these findings. There is insufficient robust evidence to suggest that genetic predispositions for VaD have any significant impact on CXCL5 (IVW: p = 0.254). The phosphate‐to‐glucose ratio accounted for 11.1% of increase in the risk of VaD associated with CXCL5 (95% CI = −12.3% to 34.5%). Conclusion To conclude, our research confirms a causal link between CXCL5 and VaD and shows that the ratio of phosphate‐to‐glucose plays a mediating role in a segment of the risk effect of CXCL5 on VaD. However, most of the effects of CXCL5 on VaD are still not well understood. Additional studies are necessary to explore other potential mediators as risk factors. In clinical settings, individuals with abnormally elevated CXCL5 may need to be monitored for an increased risk of developing VaD.